The effect of counseling on parent’s knowledge and attitudes towards stunting in toddlers: A quasi-experimental study - Cut Ridzky Amelia Putri; Husnah Husnah; Nora Sovira; Marisa Marisa; Heru Noviat Herdata (School of Medicine, Universitas Syiah Kuala, 2023)
Stunting is a condition where toddlers are too short for their age. One of the preventions is by giving health education about stunting to the parents. The aim of the study is to determine the effect of counselling on parents' knowledge and attitudes towards stunting at Lhoknga Health Center, Aceh Besar. The study was conducted from November 7 to 23, 2022. This type of study was quasi-experimental with a one-group pre-test-post-test pre-experimental design. The participants were parents who were the main caregivers of toddlers in Lhoknga Health Center area, Aceh Besar. A total of 105 respondents were recruited for this study. In regards to knowledge about stunting, pre-counseling test showed that most respondents (71.5%) had sufficient knowledge while post-test showed that all respondents (100%) had good knowledge. Meanwhile, 92.4% respondents had good attitude towards stunting prior to the counseling, and increased to 100% after the education session. The Wilcoxon test showed an increased in the average knowledge score, from 12.83 during pre-test to 18.67 on post-test. An increased in the average attitude score was also found, from 72.05 to 92.77. Statistical analysis showed that there was an effect of counseling on increasing parents’ knowledge (p0.001) and attitudes (p0.001) towards stunting. It can be concluded that counseling can increase parent's knowledge and attitudes towards stunting.